Recent Therapeutics Policies of Arthritis Rheumatoid (part I) - Andisari, Hendrata Erry (Universitas Hang Tuah, 2018)
Therapy in RA has undergone many advances today and in line with knowledge of the pathogenesis of RA, the current therapeutic goal is to alter the journey and control the activity of RA disease. Several groups of drugs have been used in RA therapy including non-steroidal anti-inflammatory drugs (NSAIDs), conventional disease-modifying antirheumatic drugs (DMARDs) as well as biological agents (bDMARD), glucocorticoids and anti-pain medicines. In recent years, the development of biological agents that have specific targets for inflammatory mediators such as interleukin (IL) -1, IL-6 and Tumor Necrosis Factor (TNF) suggests a potent therapeutic effect on RA. In this article will be presented the latest biological agents as the latest therapy on RA.